Succeeding as a young agripreneur - Pacific youth speak out - Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2019)
In the Pacific islands, where the population is expected to double by 2050, there is an urgent need for youth to become entrepreneurial and creative risk-takers to help develop innovative, and environmentally sustainable, agricultural economies. But, although more than half of the South Pacific population (10 million) is under 25 years-old, these young people are experiencing problems in entering both formal and informal labour markets. Each year, 16,000 highly skilled Pacific islanders leave their countries for better paid jobs.